2009
DOI: 10.1080/02844310902891513
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome, quality of life, patients’ satisfaction, and aesthetic results, after reduction mammaplasty

Abstract: Macromastia is a common indication for breast reduction within the public health care system in Sweden. To reduce the waiting time, a project was launched to operate on patients during a three-month period at a local hospital in Stockholm (Nacka Hospital). The operations were done by specialists and residents from the Karolinska University Hospital, using a medial flap technique. The aim of this prospective study was to evaluate the results of this project, focusing on clinical outcome, quality of life, patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 21 publications
2
40
0
Order By: Relevance
“…1 Breast reduction has been shown to improve many of the symptoms caused by macromastia, including neck, back, and shoulder pain; shoulder grooving; skin rashes; mastodynia; unwillingness to exercise; feelings of physical unattractiveness; poor sexual satisfaction; and poor quality of life. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] After breast reduction, patients are more likely to exercise and lose weight. In a survey of 41 patients, Singh et al noted that 63 percent reported reduction mammaplasty was a stimulus for weight loss, and these patients had significantly increased exercise.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…1 Breast reduction has been shown to improve many of the symptoms caused by macromastia, including neck, back, and shoulder pain; shoulder grooving; skin rashes; mastodynia; unwillingness to exercise; feelings of physical unattractiveness; poor sexual satisfaction; and poor quality of life. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] After breast reduction, patients are more likely to exercise and lose weight. In a survey of 41 patients, Singh et al noted that 63 percent reported reduction mammaplasty was a stimulus for weight loss, and these patients had significantly increased exercise.…”
Section: Discussionmentioning
confidence: 98%
“…The benefits of reduction mammaplasty include the increased ability to exercise, 12 improved quality-of-life outcomes, and overall satisfaction with breast contour. [3][4][5] Many patients undergoing breast reduction surgery, however, are obese. 17,18 Currently, there is an ongoing movement in the United States to combat obesity, with greater numbers of people undergoing bariatric procedures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In adult women, reduction mammaplasty resolves breast-related symptoms and improves self-esteem, eating behaviors, and overall HRQOL. 2,7,9,11,[16][17][18][19][20][21][22][23] Alternatively, nonsurgical methods of macromastia treatment such as weight loss have been shown to be ineffective. 4 Reduction mammaplasty, therefore, has become the standard of care for adult women with macromastia.…”
Section: Figurementioning
confidence: 99%
“…Reduction mammaplasty, surgical reduction of breast size, is the most effective means of improving symptoms and HRQOL in adults. 2,4,[6][7][8]13,14,[16][17][18][19][20][21][22][23][24][25] However, many parents and physicians are reluctant to consider surgical correction for adolescents. 26,27 Data on the impact of macromastia on younger patients are needed to better inform health care providers, patients, and families in making appropriate treatment decisions.…”
mentioning
confidence: 99%